The Conflictual Model of the Kantian Moral Philosophy - Marques, António (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This text aims to a) a reconsideration of the well-known problem in the Kantian moral philosophy regarding the moral value of the so called actions that conform with duty, but that are not done from duty, b) the clarification of problems that the Kantian solution arises related to the existence of a specific kind of conformity with duty, i.e., actions done by “immediate inclination”; typically these are actions grounded on good will and sympathy, which are good actions but without moral value, c) the demonstration that moral value requires the application of a Conflictual Model between duty and inclination, with exclusion of a Cooperation Model, d) the characterization of the moral value of action as a reflection process with a normative element. We claim that the rigorist characteristic of the Kantian moral philosophy is inherent to its system and Schiller’s critique has captured this issue with perspicuity. Yet a correct evaluation of Kant’s ethics following the Conflictual Model does not avoid and even requires such rigorism.